Stress and Coping Strategies of High School Teachers of Antique Diocesan Catholic Schools - Hazel O. Lagos, MSLT; Celo I. Magallanes (Philippine Social Science Journal, 2020)
No one is stress-free, no matter how fortunate, rational, intelligent, and knowledgeable he may be. Stress has almost become a sure thing even among Catholic school teachers. This is probably due to their demands for multiple jobs, teaching unmotivated students, maintaining classroom discipline, demanding workload, being subjected to frequent changes, being judged by others, having difficult or frustrating relationships with colleagues and administrators, and poor working conditions. Stressors faced by one teacher are unique to him or her and depend on factors like personality, beliefs, abilities, and circumstances of the teacher.  Other variables, such as coping mechanisms and techniques, personality traits, and environmental characteristics, can interactively influence the teacher's understanding of how stressful situations are.  To deal with stressful events and relieve feelings of distress, teachers use coping methods.  Rilveria (2018) identified nine coping strategies: a cognitive reappraisal, social support, problem-solving, religiosity, tolerance, emotional release, overactivity, recreation, and substance use. It has been observed that Antique Diocesan Catholic School teachers often experience high levels of stress resulting from multiple job responsibilities; thus, the researcher was propelled to explore and understand more this construct.